Lepidopteran forest defoliators in a changing climate : performance in different life-history stages, and range expansion - Fält-Nardmann, Julia (fi=Turun yliopisto|en=University of Turku|, 2018)
Although there are few confirmed records of rising temperatures contributing to range expansions and range shifts of harmful insects so far, the link between climate and insect distribution range is plausible. Temperature is likely the single most important abiotic factor limiting insect survival. Not only average temperatures but also temperature extremes, such as winter cold spells, may play an important role for insect success. As arctic and boreal regions are warming more rapidly than other regions on Earth, insects in these regions can be expected to show the greatest response to climate change. However, a warming climate may also have a negative effect on insect pests by disrupting phenological synchronies between insects and their host plants. Insects may be able to adapt to these changes genetically over generations or, more rapidly, through phenotypic plasticity – the propensity of a genotype to produce different phenotypes under different environmental conditions. In this thesis, I examine topics of climate change, insect range expansions and adaptive potential of pest insects using five univoltine spring-feeding moth species: the geometrids Epirrita autumnata, Operophtera brumata and Erannis defoliaria, and the lymantriins Lymantria monacha and L. dispar. A laboratory experiment revealed that geometrid eggs from southern populations hatch at higher temperature sums than eggs from northern populations. Following the same pattern, L. monacha from a continental European core population developed slower than their conspecifics from a boreal edge population in a field experiment. Northern moth strains may thus have genetically adapted to a shorter summer season. No local adaptation in egg supercooling points, which measure winter cold tolerance and survival, was found when comparing northern and southern strains of L. monacha. Phenotypic plasticity of the two lymantriins was studied by rearing individuals originating from the same population in climatically different locations in Germany where both species occur naturally, southern Finland where only L. monacha is confirmedly established and northern Finland where neither of the species is naturally present. Continental L. monacha appears to be less flexible than boreal L. monacha in its phenology, which may indicate that the population living on the edge of the species’ distribution range benefits from a high level of adaptive phenological plasticity that facilitates acclimation to varying environments. A rearing experiment under field conditions confirmed that both L. monacha and L. dispar can successfully complete their entire life cycle in southern Finland, and that they are not limited by host plant availability. Winter minimum temperatures are unlikely to stop L. dispar from expanding its range to southernmost Finland, although they will limit the expansion of both studied lymantriins further north. In climate warming scenarios, the northern boundary of both species’ distribution could shift by over 300 km. A recent northwards range expansion and rising abundances of L. monacha in Finland is clearly visible in observational data from both an open “Insect Database” and the systematic “Nocturna” monitoring programme. The trend started in the early 1990s and has continued since then, although with fluctuations. The observed range expansions and population growth appear to be connected to less severe winter extreme temperatures, although rising temperatures during the flight period of the species may also have contributed to its recent success. It is likely that L. monacha and L. dispar continue expanding their range and increase in abundance in Finland, and there is a risk that they become important forest pests in the country. As a preventive measure, developing a regionally adapted multilevel monitoring programme already today and promoting forest conversion from coniferous to mixed and ecologically stable stands can help reduce defoliation damage in the coming decades.

Vaikka yhteys kohoavien lämpötilojen ja tuhohyönteisten levittäytymisen välillä on toistaiseksi pystytty todentamaan vain harvoissa tapauksissa, on selvää, että ilmasto vaikuttaa hyönteisten levinneisyyteen. Lämpötila on todennäköisesti tärkein hyönteisten selviytymistä rajoittava abioottinen tekijä; keskilämpötilojen lisäksi myös äärilämpötilat, kuten talven minimilämpötilat, voivat rajoittaa hyönteisten levinneisyyttä. Lämpenevä ilmasto voi vaikuttaa tuhohyönteisiin myös negatiivisesti, jos se häiritsee hyönteisten ja niiden isäntäkasvien välistä fenologista synkroniaa. Hyönteiset voivat sopeutua muutoksiin sukupolvien saatossa geneettisillä paikallissopeumilla, tai nopeammin fenotyypin plastisuuden avulla, mikä tarkoittaa genotyypin kykyä tuottaa erilaisia fenotyyppejä erilaisissa olosuhteissa. Tässä väitöskirjassa tutkin ilmastonmuutosta sekä tuhohyönteisten levittäytymistä ja sopeutumispotentiaalia viiden yöperhoslajin avulla. Sekä mittarit Epirrita autumnata (tunturimittari), Operophtera brumata (hallamittari) ja Erannis defoliaria (pakkasmittari) että villakkaat Lymantria monacha (havununna) ja L. dispar (lehtinunna) tuottavat yhden sukupolven vuodessa ja talvehtivat munina. Laboratoriokokeessa eteläisten mittariperhospopulaatioiden munat kuoriutuivat korkeammissa lämpösummissa, toisin sanoen myöhemmin keväällä, kuin pohjoisten populaatioiden munat. Mannereuroopan ydinpopulaation havununnat kehittyivät kenttäkokeissa samoin boreaalisia lajitovereitaan hitaammin. Pohjoiset yöperhoskannat ovat siis mahdollisesti sopeutuneet lyhyisiin kesiin. Talvikaudesta selviämistä mittaavissa munien alijäähtymispisteissä ei sen sijaan ollut havaittavissa paikallisia sopeumia suomalaisten ja saksalaisten havununnapopulaatioiden välillä. Havu- ja lehtinunnien adaptiivista fenotyyppistä plastisuutta tutkittiin kasvattamalla samasta populaatiosta peräisin olevia yksilöitä ilmastoltaan erilaisilla kenttäalueilla. Keskieurooppalaisten havununnien fenotyyppi osoitti pohjoisten perhosten fenotyyppiä vähemmän joustavuutta, mikä saattaa tarkoittaa, että lajin levinneisyysalueen rajalla elävät populaatiot hyötyvät suuresta fenotyypin plastisuudesta, mikä auttaa sopeutumaan vaihteleviin olosuhteisiin. Sekä havu- että lehtinunna pystyvät onnistuneesti kehittymään munista lisääntyviksi aikuisiksi Eteläsuomessa, eikä isäntäkasvien saatavuus rajoita lajien leviämistä Suomessa. Talven minimilämpötilat rajoittanevat molempien lajien leviämistä maan pohjoisosiin. Ilmaston lämmetessä molempien lajien levinneisyysalueiden pohjoisraja saattaa siirtyä yli 300 km pohjoisemmas. Havununnan 1990-luvulla alkanut vaihtelevasti edennyt runsastuminen ja levittäytyminen kohti pohjoista näkyvätkin selvästi niin avoimen Hyönteistietokannan kuin systemaattisen seurantaohjelma Nocturnankin havaintotiedoissa. Lajin levittäytyminen ja kannan vahvistuminen vaikuttaisivat olevan yhteydessä talvipakkasten lauhtumiseen, tosin myös kesäisen lentokauden lämpötilojen nousu on saattanut vaikuttaa lajin menestykseen. Havu- ja lehtinunna todennäköisesti runsastuvat ja levittäytyvät edelleen Suomessa, ja niistä saattaa muodostua merkittäviä tuholaisia. Paikallisiin olosuhteisiin mukautettu monitasoinen seurantaohjelma sekä ekologisesti vakaita sekametsiä suosivien metsänhoidollisten toimenpiteiden käyttöönotto mahdollisimman pian ovat suositeltavia keinoja vähentää tulevaa tuhoriskiä.